Exploring Happiness in the Islamic Tradition: Nawawi al-Bantani’s Ethical Vision through Gadamer Hermeneutics - Mahfudhoh, Umi; Abdullah Khozin Afandi (Faculty of Ushuluddin and Philosophy, 2023)
The concept of happiness is an intriguing topic, with various interpretations from each individual. Some people associate happiness with material wealth, social status, or academic achievement, while others find happiness through simple experiences. This concept of happiness, which has been debated since ancient times, was initially more often associated with hedonism, namely the pursuit of pleasure as the goal of life. However, true happiness does not lie in external factors, but rather comes from within the human being. The pursuit of happiness that depends on external factors often leads to dissatisfaction and is temporary. This article examines Sheikh Nawāwī al-Bantānī’s view of happiness, which states that true happiness is possessed by those who have awareness of the heart, patience of the body, and gratitude for all that they have. This study uses Hans-Georg Gadamer’s hermeneutic theory to understand Sheikh Nawāwī’s thoughts on happiness, emphasizing the importance of historical and linguistic context in text interpretation. The results show that, according to Sheikh Nawāwī, happiness is achieved through patience, awareness of Allah’s presence, and a deep sense of qanā‘ah towards all His gifts.